Visual Identity for the Red Umbrella Iceland - Kirstin Natalija Stojadinović 1995- (2022)
What does it mean to be a sex worker in Iceland today? At best you get stigmatised and at worst you could lose your livelihood or get deported. Sex work has largely been forced underground and therefore isn't visible in our society which makes it hard to connect with other sex workers without outing yourself. Founded by sex workers for sex workers, Rauða regnhlífin is an organisation which provides a safe place to turn to and aims to educate and shine a light on the struggles sex workers face. The project's goal was to create a visual identity that would honour the grassroots origins of sex work activism and while forming a voice of credibility.